2006
DOI: 10.1037/0278-7393.32.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative differences between implicit and explicit sequence learning.

Abstract: Four experiments investigate the differences between implicit and explicit sequence learning concerning their resilience to structural and superficial task changes. A superficial change that embedded the SRT task in the context of a selection task, while maintaining the sequence, did selectively hinder the expression of implicit learning. In contrast, a manipulation that maintained the task surface, but decreased the sequence validity, affected the expression of learning specifically when it was explicit. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 38 publications
7
95
0
3
Order By: Relevance
“…This detrimental effect of intentional search or divided attention on the expression, but not acquisition of learning, has been demonstrated in the past Jimenez et al, 2006). The fact that in the present experiment continued search did not impair expression in the Respond groups suggests that learning based on motor responses is less sensitive to the effects of divided attention and explicit search.…”
Section: Discussionmentioning
confidence: 35%
See 1 more Smart Citation
“…This detrimental effect of intentional search or divided attention on the expression, but not acquisition of learning, has been demonstrated in the past Jimenez et al, 2006). The fact that in the present experiment continued search did not impair expression in the Respond groups suggests that learning based on motor responses is less sensitive to the effects of divided attention and explicit search.…”
Section: Discussionmentioning
confidence: 35%
“…Our goal was to see if continued search for the pattern affected the expression of perceptual or motor based learning. Engaging in intentional search often interferes with expression of implicit learning although not its acquisition (Jimenez et al, 2006;Song et al, 2007). In this manner, in addition to asking whether implicit sequence learning could occur via observation alone, we could assess whether intentional search had an effect on the expression of such learning.…”
Section: Methodsmentioning
confidence: 99%
“…Single-system views predict that fostering or hindering explicit knowledge respectively increases or decreases the amount of implicit learning (Jiménez, Vaquero & Lupiáñez, 2006;Sanchez & Reber, 2013). In our study, incidental and intentional (implicit and explicit) learners were similar in their inability to express temporal learning under a complex ordinal load, as well as in their ability to do it under simple load.…”
Section: Ordinal Load and Incidental Temporal Learning ! 22mentioning
confidence: 61%
“…Thus, the same strategic factor (ordinal load complexity) that controlled the expression of explicit knowledge controlled the expression of implicit knowledge too (Jiménez et al, 2006). This speaks in favour of a single (implicit-explicit) memory system, possibly showing different outputs depending on the means used for probing acquired knowledge (Jamieson & Mewhort, 2009).…”
Section: Ordinal Load and Incidental Temporal Learning ! 22mentioning
confidence: 99%
“…More recently, Jiménez, Vaquero and Lupiáñez (2006) have shown that participants trained on an SRT task under intentional conditions, in which they were instructed to search for sequences, were able to transfer their sequence learning when the task's surface features were changed, while incidental learners were not. On the other hand, when the transfer test retained the surface features but involved a substantial reduction in the proportion of trials that were consistent with the sequence, incidental learners showed transfer of learning while intentional learners did not, presumably because the latter withheld expression of their sequence knowledge.…”
mentioning
confidence: 99%